2006
DOI: 10.1111/j.1945-5100.2006.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact craters in the northern hemisphere of Mars: Layered ejecta and central pit characteristics

Abstract: Abstract-Mars Global Surveyor (MGS) and Mars Odyssey data are being used to revise the Catalog of Large Martian Impact Craters. Analysis of data in the revised catalog provides new details on the distribution and morphologic details of 6795 impact craters in the northern hemisphere of Mars. This report focuses on the ejecta morphologies and central pit characteristics of these craters. The results indicate that single-layer ejecta (SLE) morphology is most consistent with impact into an ice-rich target. Double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 52 publications
10
71
2
Order By: Relevance
“…Some craters on Mars also exhibit central pits on top of central peaks which are not seen on Ganymede (Barlow, 2006). If central pits on Mars were formed via molten rock draining through solid rock, we would expect the pit volumes to fall somewhere in between the estimated drainage volumes on Earth and the Moon, because gravity is the only difference.…”
Section: Marsmentioning
confidence: 92%
See 1 more Smart Citation
“…Some craters on Mars also exhibit central pits on top of central peaks which are not seen on Ganymede (Barlow, 2006). If central pits on Mars were formed via molten rock draining through solid rock, we would expect the pit volumes to fall somewhere in between the estimated drainage volumes on Earth and the Moon, because gravity is the only difference.…”
Section: Marsmentioning
confidence: 92%
“…However, in large craters (D > 100 km) the central uplift will be made of mostly dry rocks initially located below the aquifer (Ivanov and Pierazzo, 2011). This may explain why central pits do not occur in craters with diameters larger than 114 km on Mars (Barlow, 2006). In Martian craters smaller than 100 km in diameter, central pits could form through the removal of volatile materials near the crater center by vaporization during the impact or if liquid water pools in the center of the crater, it could drain without solidifying since the high initial fracture wall temperature will not allow the fluid to cool.…”
Section: Marsmentioning
confidence: 93%
“…So-called ramparts or ridges, the origin of which is debated, are often seen at the outer edge(s) of the ejecta layers. DLE craters remain enigmatic but are most common in mid-latitude regions (Barlow, 2006). It is widely accepted that layered ejecta deposits were highly fluidized at the time of their emplacement and occurred as relatively thin groundhugging flows (Carr et al, 1977).…”
Section: Marsmentioning
confidence: 99%
“…Furthermore, several sub-populations have been recognised, including low-aspect-ratio layered ejecta craters (LARLE) Boyce, 2012, 2013) and excess ejecta craters (EEC) (Black and Stewart, 2008). Perched craters (Pr) (Boyce et al, 2005;Garvin et al, 2000) and pedestal craters (Pd) (Barlow, 2006;Kadish et al, 2009) have also been identified as potential erosional end-members of some layered craters in icy terrains where significant volumes of material have been removed (Kadish et al, 2009;Meresse et al, 2006). The significant heterogeneity within each type of fluidized crater morphology is not fully understood and is difficult to explain through any single formation model.…”
Section: Introductionmentioning
confidence: 99%